The Spatial Impact of PM2.5 Pollution on Economic Growth from 2012 to 2022: Evidence from Satellite and Provincial-Level Data in Thailand - Thanakhom Srisaringkarn; Kentaka Aruga (Urban Science)
This study examines the spatial relationship of PM2.5 concentrations across provinces in Thailand and explores the relationship between socio-economic factors and PM2.5 levels from 2012 to 2022. The study results indicate that PM2.5 pollution in Thailand is spatially clustered, meaning that PM2.5 spills over into nearby provinces and is not confined to a single area. The factors that positively affect PM2.5 concentrations include population density and energy consumption per capita, while industrial density has a negative effect on PM2.5 levels. Additionally, an Environmental Kuznets Curve (EKC) analysis found that the Gross Provincial Product (GPP) per capita has a U-shaped relationship with the PM2.5 concentration. In the initial stage of economic growth, as the GPP per capita increases, PM2.5 concentrations gradually decrease. However, once income reaches USD 56,715 and the economy becomes significantly large, further increases in GPP per capita lead to rising PM2.5 concentrations. In other words, during the early phase of economic development, PM2.5 pollution does not intensify significantly. However, once Thailand’s economy reaches a certain scale, continued economic expansion exacerbates PM2.5 pollution, leading to greater economic and social consequences. The study highlights the importance of integrated collaboration among various organizations in mitigating the widespread impacts of PM2.5 pollution.